Experimental investigation of hybrid thermoelectric evaporative air-cooling system for crickets rearing process - Peeradapath Parametpisit; Piyapat Panmuang; Amornthep Sonsilphong; Chaiyong Soemphol (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Due to the effects of the change in temperature that have resulted in dramatic changes in the livelihoods of crickets. Hence, the implementation of cooling technologies is an important factor for alleviating these negative consequences. This research presents the experimentally investigate the feasibility of employing a thermoelectric cooler in combination with an evaporative air-cooling system for two-spotted cricket (Gryllus bimaculatus) rearing process. The proposed cooling system has been installed to reduce the temperature that appropriate for the cricket rearing. The experimental results show that the product air temperature of cricket rearing pens with thermoelectric evaporative air-cooling system decreases form ambient air. The average temperature of the cricket rearing pens with thermoelectric evaporative air-cooling system is 29.66 °C, with the highest temperature at 31.40 °C. While the average temperature of the cricket rearing pens without thermoelectric evaporative air-cooling system is 33.75 °C, with the highest temperature at 37.10 °C. Furthermore, this research also shows that this proposed system can improve cricket survival rate. The crickets that reared in the prototype system have a survival rate of 88.5%, while survival rate of crickets in an uncontrolled pen is 67.2%. This paper provides a potential of applying thermoelectric evaporative air-cooling for cricket farming.